3-Dimensional numerical modeling of geosynthetic-encased granular columns. Issue 3 (June 2017) - Mohapatra, Sunil Ranjan; Rajagopal, K.; Sharma, Jitendra
Abstract: In this paper, series of three-dimensional (3-d) numerical modeling of geosynthetic-encased granular columns were performed both in model and prototype scale using FLAC 3D software to understand the lateral load carrying capacity of ordinary and geosynthetic encased granular columns (OGC and EGC). In the first part of the study, numerical modeling of direct shear tests were carried out. The soil in the direct shear box was reinforced with two different diameters of granular columns (50 mm and 100 mm) and three different patterns of arrangement (single, triangular and square) to study the effect of group confinement. The numerical simulations were carried out at four different confining pressures namely 15, 30, 45 and 75 kPa. From the numerical simulations it was observed that higher shear stresses are mobilized inside the granular column due to geosynthetic encasement and the magnitude of shear stress increases with increase in the normal pressure. It was found that the tensile forces in the geosynthetic encasement were mobilized both in circumferential and vertical directions, which helps in mobilizing additional confinement in the granular column. In the second part, the influence of the geosynthetic encasement of granular column treated soft ground was demonstrated through 3-dimensional slope stability analyses.